Life Underground: Investigating Microbial Communities and Their Biomarkers in Mars‐Analog Lava Tubes at Craters of the Moon National Monument and Preserve. Issue 11 (25th November 2022) - Weng, M. M.; Zaikova, E.; Millan, M.; Williams, A. J.; McAdam, A. C.; Knudson, C. A.; Fuqua, S. R.; Wagner, N. Y.; Craft, K.; Kobs Nawotniak, S.; Shields, A.; Bevilacqua, J.; et al.
Abstract: Craters of the Moon National Monument and Preserve (CotM) is a strong terrestrial analog for lava tube formations on Mars. The commonality of its basalt composition to Martian lava tubes makes it especially useful for probing how interactions between water, rock, and life have developed over time, and what traces of these microbial communities may be detectable by current flight‐capable instrumentation. Our investigations found that secondary mineral deposits within these caves contain a range of underlying compositions that support diverse and active microbial communities. Examining the taxonomy, activity, and metabolic potential of these communities revealed largely heterotrophic life strategies supported by contributions from chemolithoautotrophs that facilitate key elemental cycles. Finally, traces of these microbial communities were detectable by flight‐capable pyrolysis and wet chemistry gas chromatography‐mass spectrometry methods comparable to those employed by the Sample Analysis at Mars (SAM) instrument aboard the Curiosity rover and the Mars Organic Molecule Analyzer (MOMA) on the upcoming Rosalind Franklin rover. Using a suite of methods for chemical derivatization of organic compounds is beneficial for resolving the greatest variety of biosignatures. Tetramethylammonium hydroxide (TMAH), for example, allowed for optimal resolution of long chain fatty acids. Taken together, these results have implications for the direction of mass spectrometry as a tool for biosignature detection on Mars, as well as informing the selection of sampling sites that could potentially host biosignatures. Plain Language Summary: We investigated lava tubes at Craters of the Moon National Monument and Preserve for their potential to host and preserve evidence of life. Lava tubes are found on both Earth and Mars, and can shield life from extreme environmental conditions such as radiation and temperature fluctuation. We found a variety of mineral deposits on the walls of lava tube caves formed by water‐rock interactions throughout time, which hosted diverse microbial communities. These communities contained the ability to generate energy from both inorganic and organic carbon sources, as well as cycle important nutrients such as nitrogen and sulfur. In addition, we used techniques comparable to those employed aboard the Sample Analysis at Mars instrument on the Curiosity rover to understand whether this life could hypothetically be detected by exploratory missions. Many organic molecules were detected using our techniques, demonstrating that these habitats have the potential to preserve life and its traces on other worlds. Key Points: Genomic results reveal a diverse microbial ecosystem in the lava tubes at Craters of the Moon There are multiple ways for chemolithotrophic life to harvest energy in this basaltic Mars analog environment Biosignatures, or traces of life, can be detected in secondary mineral deposits using flight‐like techniques